"Alert"-технології, що грунтуються на теорії динамічних систем в економічних задачах - Lopatin, A. K. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2017)
An "Alert"-technology (prevention technology) for economic and financial processes, which is given by numerical series, is proposed. Іt is shown that on the basis of the proposed methodology of using the Lyapunov’s leading indicators, it is possible to create the effective "Аlert"-technology of detection of critical phenomena in the economic and financial processes.